GROUP COLLABORATIVE CHALLENGES IN TODAY'S - Campbell, Mr. Andrew (IJRDO - Journal of Applied Management Science, 2016)
This paper examines the collaborative challenges of organizational intergroup andintergroup dynamics. Research shows that collaborative networks are a strategic asset used byfirms that form as alliances and partnerships to develop new products and services in sustaining acompetitive advantage (Provan & Kenis, 2007). This paper argues that collaborativerelationships are challenging. The challenge of leader-follower relationships, group membersthat represent organizational interests, transnational coordination, and intergroup conflictcompounds the firm’s collaboration outcomes. The author addresses negotiation strategies forproblem solving, and conflict resolution to enhance collaborative efforts within the organization.